STATE RESPONSIBILITY AND INTERNATIONAL ORGANIZATIONAL IMMUNITY: A CASE STUDY OF THE MOTHER SREBRENICA IN THE UN SAFE ZONE - Hengki, (JIL : Journal of Indonesian Law, 2025)
This research aims to analyze form of legal responsibility of the Dutch state and the United Nations (UN) for the failure to protect civilians in the Srebrenica genocide tragedy, emphasizing the principle of due diligence, concept of effective control, and the doctrine of loss a chance. The method used is normative juridical with a case approach, through study of the decision Dutch Supreme Court and analysis of international legal instruments such as Articles on the Responsibility of States for Internationally Wrongful Acts (ARSIWA) and Articles on the Responsibility of International Organizations (ARIO). The results show that the Dutch state can be held legally responsible for actions of its troops (Dutchbat) because it had effective control during the evacuation of victims, while the UN cannot be held legally responsible due to institutional immunity barriers. These findings indicate an accountability gap in the international legal system that hinders the fulfillment rights to justice and reparations of victims. Therefore, reforms to immunity structure of international organizations are needed to strengthen accountability mechanisms in peacekeeping missions.